2018
DOI: 10.1007/s00464-018-6106-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining minimal clearances for adequate lymphatic resection relevant to right colectomy for cancer: a post-mortem study

Abstract: Right colonic lymphovascular bundles are volumes of mesenteric tissue that surround the superior mesenteric vessels anteriorly and posteriorly. Long lymphatic vessels traverse the superior mesenteric vein anteriorly/posteriorly approaching the superior mesenteric artery between arterial bundles and placing the medial clearance on the left side of the artery. These do not correlate to arterial crossing patterns. Cranial-caudal clearances determine the tissue to be removed superior/inferior to arterial origins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
1
36
1
Order By: Relevance
“…The concept of CME introduced standardized colon cancer surgery with resection in the mesocolic plane and central ligation of the tumor feeding vessel [1]. In recent years, there has been significant debate about the clinical benefit of CME surgery and specifically mandatory division of the tumor feeding artery remains controversial [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of CME introduced standardized colon cancer surgery with resection in the mesocolic plane and central ligation of the tumor feeding vessel [1]. In recent years, there has been significant debate about the clinical benefit of CME surgery and specifically mandatory division of the tumor feeding artery remains controversial [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The medial border follows a line running along the left border of the SMA. 8 Because this is the pathway for the SMP, one must assume that most of the nerves belonging to the plexus at this level are transected. The procedure is significantly more radical than the traditional lymphadenectomy, including the so-called complete mesocolic excision (Fig.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…To improve the oncological outcomes of colon cancer, the focus has turned toward more radical lymphadenectomy. 8 In the case of the right colon, this leads us directly into the common neurovascular stem of the midgut containing the extrinsic nerve plexus 2 . Based on theoretical considerations and constraints, surgeons were hesitant to enter this area.…”
Section: Introductionmentioning
confidence: 99%
“…Until now the internal border of the central area has remained fuzzy, and the data on regional LNs around superior mesenteric vessels are scanty [8,9]. Currently, most surgeons de ne SMV as the destination of RCC surgery, but this opinion is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Milan Spasojevic et al reported an anatomical postmortem study and established the presence of LNs posterior to SMV, which was associated with the cross-modal relationship between an ileocolic artery (ICA) and SMV [10]. Recent postmortem research developed the understanding that the long right colonic lymphovascular bundles were across the SMV and described the midline of SMA as the watershed between the small bowel and right colon lymphatics [8]. This research had shown the potential necessity to de ne the internal border of RCC resection to the midline of SMA.…”
Section: Introductionmentioning
confidence: 99%